Thermal Analysis And Performance Of An Active Solar Dryer System Based On Solar Panels For Improving The Quality Of Cocoa Bean Drying - Nely Ana Mufarida; Sofia Ariyani; Nurhalim; Sutikno; Ulya Anisatur Rosydah (Universitas Muhammadiyah Ponorogo, 2026)
Cocoa is one of Indonesia’s leading agricultural commodities and plays a strategic role in increasing national foreign exchange earnings. However, the low quality of Indonesian cocoa beans remains a major obstacle in penetrating the export market. This issue is largely caused by post-harvest drying processes that still rely on traditional sun-drying methods. Dependence on weather conditions often results in cocoa beans failing to reach the ideal moisture content (6–8%), making them susceptible to mold growth, deterioration, and reduced quality. These conditions ultimately lower the market value and competitiveness of Indonesian cocoa in the global market.This study aims to develop a direct-type active solar dryer technology powered by solar energy to improve drying efficiency and preserve the quality of cocoa beans. The system is designed using a combination of solar panels, heating elements, and exhaust fans controlled to regulate temperature, humidity, and airflow optimally throughout the drying process. The methodology includes design engineering, thermal simulation, and experimental testing to determine the best operating conditions that ensure fast drying, energy efficiency, and maintained physical and chemical quality of the cocoa beans. This research is expected to serve as an innovative step in the application of renewable energy in the agricultural sector, contributing to improved productivity and sustainable competitiveness for Indonesian cocoa farmers.